PROTOTIPE SISTEM PULLY MEKANIK HIGH TORQUE PENGGERAK ALAT PEMBERSIH PANEL SURYA OTOMATIS DENGAN MASSA 40 KG - Rakhmat, Riko; Repelianto, Ageng Sadnowo; Setyawan, FX Arinto; Fitriawan, Helmy; Sulistiyanti, Sri Ratna (Universitas Teknokrat Indonesia, 2024)
Solar energy is one of the New Renewable Energy (EBT) which is used specifically to meet electrical energy needs by converting it using a device often called a solar panel. Solar panels are generally arranged in PLTS in open areas so they have the potential to be exposed to dirt such as dust which can accumulate over a certain time and cause a reduction in the efficiency of sunlight irradiance on the surface of the solar panels. The solar panel cleaning system in solar power plants (PLTS) usually still uses conventional methods, namely cleaning by human power. In current technological developments, many automatic cleaning tools have been developed, but most of them in the field are only able to support a tool mass of under 10 kg. To clean a large 330 Wp solar panel, a frame construction is needed as a panel holder that can support a device mass of more than 10 kg, so in this paper a solar panel frame is designed that can support a weight of up to 40 kg. This tool is designed with a mechanical system that is able to support a larger mass of tools than is generally available in the field. In terms of mechanical system, the frame design of this tool uses a rectangular shape with hollow iron material to maintain a balanced position and is driven by a motor with a pully system as a kinetic energy transmission system for rotational motion using a High Torque motor. From the research results, it was found that the tool was able to work with a mass of 40 kg, a power consumption of 53.15 Watts with a tool operating time of 4 hours.